2020
DOI: 10.1111/coa.13574
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve using the Sunnybrook Facial Grading System in assessing facial palsy: An observational study in 100 patients

Abstract: Assessment of facial function in facial palsy patients is important to evaluate current status and treatment effect. The Sunnybrook Facial Grading System (SB) is one of the clinician grading's of facial function. 1 Inter-and intraobserver reliability ranges from 0.838 to 0.980 and 0.831 to 0.997, respectively. 2 However, most reliability studies included experienced observers. In research projects, facial palsy assessment is often done by medical students. Additionally, general practitioners and starting resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…11,25 Although we did not assess interobserver agreement, our findings are aligned with previous studies that have found strongest interrater reliability of both the House-Brackmann and Sunnybrook scale among senior clinicians compared to juniors or inexperienced medical students. 26,27 Importantly, in a post hoc analysis we found that agreement between the 2 scales dropped from excellent to moderate when observations with a House-Brackmann score of I were removed from the analysis. This means that the scales moderately agree in patients with disease, and agreement improves in the absence of disease.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…11,25 Although we did not assess interobserver agreement, our findings are aligned with previous studies that have found strongest interrater reliability of both the House-Brackmann and Sunnybrook scale among senior clinicians compared to juniors or inexperienced medical students. 26,27 Importantly, in a post hoc analysis we found that agreement between the 2 scales dropped from excellent to moderate when observations with a House-Brackmann score of I were removed from the analysis. This means that the scales moderately agree in patients with disease, and agreement improves in the absence of disease.…”
Section: Discussionmentioning
confidence: 82%
“…11,25 Although we did not assess interobserver agreement, our findings are aligned with previous studies that have found strongest interrater reliability of both the House-Brackmann and Sunnybrook scale among senior clinicians compared to juniors or inexperienced medical students. 26,27…”
Section: Discussionmentioning
confidence: 99%
“… 18 Greater variability in the assessment of facial function has been reported between senior clinicians compared to juniors and medical students. 19 , 20 Increasing familiarity with the scales and greater familiarity with facial movement deficits by parents may also explain the improving agreement over time. In our study some of the follow‐up assessments may have been conducted by a different caregiver from the one who completed the baseline assessment.…”
Section: Discussionmentioning
confidence: 99%
“…This shortcoming may be particularly relevant for the initial clinician assessment in the ED where junior clinicians may have graded participants. 19 , 20 We only assessed agreement between the scales in children with Bell's palsy though the results are likely applicable to other causes of FNP. The parent‐administered House‐Brackmann scale will need to be externally validated to support its broader use.…”
Section: Limitationsmentioning
confidence: 99%
“…This scale includes 13 items, among which three are resting, five are related to voluntary movement, and five are about synkinesis movement. The total score ranges from 0-100, among which the score range for resting symmetry is 0-20, the score range for voluntary symmetry is 20-100, and synkinesis is 0-15 [8,9].…”
Section: Outcome Measuresmentioning
confidence: 99%